Perbandingan Hubungan Industrial dalam Hukum Ketenagakerjaan Indonesia dan Malaysia: Pekerjaan Layak bagi Pekerja Migran Indonesia (PMI) - Yeski Utami; Suartini (JURNAL ILMIAH EDUNOMIKA, 2026)
This study aims to analyze the implementation of industrial relations for Indonesian Migrant Workers (PMI) in Malaysia using a decent work indicator approach, both prioritized and marginalized in the migration decision-making process. This study uses a normative-empirical legal research method, which combines an analysis of labor laws and regulations in Indonesia and Malaysia, including bilateral Memorandum of Understanding (MoU), with empirical findings in the field. Empirical data were obtained through in-depth interviews with 30 PMIs working in the formal sector in Malaysia, who were selected purposively. The results show that decent work indicators that are the main priority for PMI include legal employment opportunities, relatively higher income, more regular working hours, and access to basic social security for legal migrant workers. These indicators are perceived to provide direct economic benefits and certainty of employment status, thus becoming the dominant factors driving migration to Malaysia. In contrast, decent work indicators related to long-term social protection and worker participation—such as job stability and security, work-life balance, a preventatively safe work environment, and social dialogue and worker representation—tend to be marginalized by migrant workers. Although both countries have legal frameworks that are relatively aligned with International Labour Organization (ILO) standards, their implementation remains selective and does not fully protect the interests of migrant workers. This study concludes that Indonesia–Malaysia transnational industrial relations function more as a migrant worker management mechanism than as a comprehensive protection instrument. Keywords: Indonesian Migrant Workers (PMI), Decent Work, Industrial Relations, Employment